Analisis Pengaruh Kesadaran Lingkungan dan Harga Premium terhadap Niat Beli Produk Hijau di Pontianak - Pebrianti, Wenny (Fakultas Ekonomi dan Bisnis, UNTAN, 2012)
The purpose of this research is to determine whether there is influence of environmental awareness and premium prices to purchase intentions of green product for organic vegetable and fruit product in Pontianak. The total of sample are 93 people who domicile at Pontianak. The collecting data method uses interview and survey study. Method of data analysis uses statistic descriptive analysis and multiple linear regression analysis. The result of this research shows that environmental awareness and premium price variables influence simultaneously to purchase intention of green product. The result of the partial is same also that both of variables like environmental awareness and premium influence significantly to purchase intention of green product. The amount of determinant coefficient (R2) 0,414 or 41,4% means the ability of explaining the influence environmental awareness and premium price variables to purchase intention of green marketing while the remaining is influenced by others independent variables which are not examined in this research. Keywords : Environmental Awareness, Premium Price and Purchase Intention of Green Product